Exit Survey-Based Assessment for Continuous Quality Improvement of the Diploma in Civil Engineering Program at Mukah Polytechnic (Borneo Engineering & Advanced Multidisciplinary International Journal, 2025)
The lack of empirical data on graduating students’ attainment of all twelve Programme Learning Outcomes in Politeknik Mukah’s Diploma in Civil Engineering programme constrains evidence-based verification against Engineering Accreditation Council requirements. This evidentiary gap jeopardises the programme accreditation credibility and blunts strategic quality improvement initiatives that ensures graduates are industry ready. As such, this study evaluates the effectiveness of Politeknik Mukah’s Diploma in Civil Engineering programme by analysing exit-survey responses from the 2021/2022 graduating cohort. Correspondingly, the primary objective is to assess students' perceptions attainment of Programme Learning Outcomes (PLOs) and core graduate attributes in line with the Outcome-Based Education (OBE) framework and Continuous Quality Improvement (CQI) practices. Additionally, this study examined 94 students who completed Diploma in Civil Engineering programme during Session II 2021/2022. Seventy-nine survey items that grouped into job skills, soft skills, instructional effectiveness, and campus services, were analysed descriptively in Microsoft Excel and SPSS.  Subsequent, this study has found that the respondents rated their achievement in all 12 PLOs as high, with the highest score recorded for PO9: Individual and Team Work (mean: 4.28) and PO8: Ethics (mean: 4.11). The core graduate attributes, particularly critical thinking (mean: 3.95), job skills (mean: 4.04), and instructional effectiveness (mean: 4.11) also earned strong rating. Some areas were identified for improvement include entrepreneurial skills (mean: 3.69), support services, and campus facilities. The results underscore the program’s overall effectiveness in preparing students with technical competence, ethical awareness, and soft skills required for industry and lifelong learning. Overall, this study recommends targeted enhancements in infrastructure, student support, and curriculum design to ensure continuous improvement and sustained program quality.